The Need to Integrate Fundamental Radiology in Undergraduate Medicine Curriculum - Masood, Muhammad Hamza; Khan, Dilawar Ali (Annals of King Edward Medical University, 2023)
Dear Editor, Since its advent in the early Twentieth Century, Radiology beholds capital significance in diagnostic and therapeutic medicine. Imaging techniques of the likes of X – Ray, CAT scan, MRI and the positron emission tomography (PET) have taken the world by storm over the past 20 years so much so that they have become indispensable in Medical Investigation. There is a growing school of thought with the view that basic radiological knowledge of X – Rays and Ultrasound should be imparted to medical students from the get-go.1 As a matter of fact, until recently an overwhelming majority of Medical Institutions in Pakistan have been adherent to the orthodox Non - Modular system which was essentially based on the then transformative Flexner Report of July 1910 where Abraham Flexner vehemently advocated learning basic biomedical sciences prior to clinical sciences; thereby preferring less practical theoretical knowledge to that of empirical importance to the clinician.2 Unfortunately, that is not how patients are to be treated.3 Recently, all Medical Colleges under University of Health Sciences have adopted the Integrated Modular system4 which endorses the studying of basic and clinical subjects side by side. In addition to this much needed step, the concerned authorities are exhorted to look into the need to include fundamental radiological techniques in the under graduate Medical curriculum in order to properly integrate the modular system.